2007
DOI: 10.1016/j.bbabio.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Artificial model of photosynthetic oxygen evolving complex: Catalytic O2 production from water by di-μ-oxo manganese dimers supported by clay compounds

Abstract: Adsorption of [(OH(2))(terpy)Mn(mu-O)(2)Mn(terpy)(OH(2))](3+) (terpy=2,2':6',2"-terpyridine) (1) onto montmorillonite K10 (MK10) yielded catalytic dioxygen (O(2)) evolution from water using a Ce(IV) oxidant. The Mn K-edge X-ray absorption near edge structure (XANES) of the 1/MK10 hybrid suggested that the oxidation state of the di-mu-oxo Mn(2) core could be Mn(III)-Mn(IV). However the pre-edge peak in the XANES spectrum of 1 adsorbed on MK10 is different from the neat 1 powder. The kinetic analysis of O(2) evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The assumed active species were [Mn 2 IV O 2 (L) 4 ] 4+ . However, these results have never been corroborated 57. The instability of [Mn 2 III,IV O 2 (L) 4 ] 3+ in an aqueous solution, except in a L/LH + buffer, as well as the evolution of its one‐electron oxidized form into a stable tetranuclear species makes the involvement of [Mn 2 III,IV O 2 (L) 4 ] 3+ as an active catalyst for water oxidation questionable 40–42.…”
Section: Polypyridyl Complexes (Bipyridine Phenanthroline and Termentioning
confidence: 99%
See 2 more Smart Citations
“…The assumed active species were [Mn 2 IV O 2 (L) 4 ] 4+ . However, these results have never been corroborated 57. The instability of [Mn 2 III,IV O 2 (L) 4 ] 3+ in an aqueous solution, except in a L/LH + buffer, as well as the evolution of its one‐electron oxidized form into a stable tetranuclear species makes the involvement of [Mn 2 III,IV O 2 (L) 4 ] 3+ as an active catalyst for water oxidation questionable 40–42.…”
Section: Polypyridyl Complexes (Bipyridine Phenanthroline and Termentioning
confidence: 99%
“…This was the first di‐μ‐oxido complex considered as a structural model for the manganese complex in the OEC that could carry out catalytic O–O bond formation. However, the real source of oxygen atoms for O 2 evolution has been debated, since KHSO 5 and NaOCl are also oxygen‐atom‐transfer reagents 2,57. Some attempts have also been reported using a pure electron‐transfer oxidizing agent like Ce IV .…”
Section: Polypyridyl Complexes (Bipyridine Phenanthroline and Termentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23] We reported the heterogeneous water oxidation catalysis of 1 ads on layer compounds such as kaolin, mica and montmorillonite (Mt). [26,[40][41][42] The kinetic analysis of O 2 evolution suggested that the catalysis requires cooperation of two 4 equivalents of 1 ads on layer compounds. The heterogeneous catalytic activity of the derivatives with R-terpy ligands (R= butoxy, propoxy, ethoxy, methoxy, methyl, methylthio, chloro and pyridyl) are quite different, showing that the catalytic activity strongly depends on the structure of complexes adsorbed [43].…”
Section: Introductionmentioning
confidence: 99%
“…or Mn 3+ ions does not work for water oxidation at all [26,[40][41][42]. They suggested from their X-ray absorption spectroscopic and O 2 evolution data that 1 is transformed on Mt into layered type manganese-oxide particles which are the actual water oxidation catalyst.…”
mentioning
confidence: 99%